FCSIT Research Bulletin 2016 - Universiti Malaysia Sarawak, Faculty of Computer Science and Information Technology (UNIMAS Publisher, 2016)
The FCSIT Research Bulletin is an annual publication of the Faculty of Computer Science and Information Technology, UNIMAS. The purpose of FCSIT Research Bulletin is to disseminate information that represent the current state of the research activities, publications, research findings, training, conferences and seminar conducted by the academicians in the faculty.